A technique of dispatching algorithms for web-server cluster system - Zarina Mohamad (2004)
Providing reliable and efficient services are primary goals in designing a webserver cluster (WSC). Data replication techniques can be used to improve thereliability of the system. One of the techniques is Neighbor Replica DistributionTechnique (NRDT). Domain Name Server (DNS) is one of the software used formanaging request information from users. However, DNS is not suitable for theNRDT of managing data replication. This thesis proposes web cluster architecturebased on NRDT to enhance DNS. This concept is called NRDT-DNS. Thefunction ofNRDT-DNS is to dispatch any user requests through a host name to IPaddressmapping mechanism. This technique enables services from one node to be